LO74: Prehospital sodium bicarbonate use was associated with worse neurological outcomes among patients with out-of-hospital non-traumatic cardiac arrest. (15th May 2017) - Kawano, T.; Scheuermeyer, F.X.; Christenson, J.; Stenstrom, R.; Grunau, B.E.
Abstract : Introduction: Sodium bicarbonate (SB) is still widely used for resuscitation in out-of- hospital cardiac arrest (OHCA) despite limited clinical indications but the effect on neurological recovery is unclear.Methods: From 2006 to 2016, we prospectively conducted a province-wide population-based observational study of adult non-traumatic OHCA patients managed by EMS. According to provincial guidelines, paramedics administered SB to OHCA patients based on their clinical assessment. Outcome of interest was favorable neurological outcome at hospital discharge, defined as CPC of 1 and 2 or modified Rankin scale of 3 or less. We performed multivariable logistic regression, comparing the proportion of outcome between SB and non-SB groups, further stratified by the median of the length of resuscitation. We also applied propensity score matching technique adjusting for baseline characters to the same model to reduce potential selection bias.Results: Of 13, 008 OHCA patients, 4, 699 (36.1%) were managed with SB. In the SB treated group, 64 / 4, 699 (1.3%) patients had favorable neurological outcomes, compared to 823 / 8, 309 (9.9%) in the non-SB treated group (crude odds ratio [OR] 0.12, 95% CI 0.09 to 0.16). In logistic regression model, SB was associated with decreased probability of favorable outcomes (adjusted OR 0.63, 95% CI 0.45 to 0.89). Similarly, with stratification by length of resuscitation, the SB group had a lower probability of favorable outcomes (≦24 min: adjusted OR 0.68, 95% CI 0.46 to 1.02, >24 min: adjusted OR 0.47, 95% CI 0.23 to 0.97). In 1:1 propensity matched cohort including 5, 126 OHCA patients, the adjusted association also persisted (adjusted OR 0.59, 95% CI 0.39 to 0.89).Conclusion: Prehospital administration of SB to OHCA patients was associated with worse neurological outcomes and the trend persisted even after stratification by resuscitation length.